2019
DOI: 10.1080/1354571x.2019.1576418
|View full text |Cite
|
Sign up to set email alerts
|

Women helping women? Chain of command and gender discrimination at the workplace

Abstract: We analyse how the gender composition of the Board of Directors and of the management affects the hiring and promotion decisions by gender in large private Italian firms. We observe a disproportionate share of men hired and promoted, regardless of the top ranks' gender composition. However, a mitigating effect is detected due to the presence of women in higher managerial ranks that increases promotions of women in lower ranks consistently with the 'women helping women hypothesis'. However, this mitigating effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Another study conducted by Verma., N. (2015) [18] found gender discrimination exists in senior management positions in top 50 American sample companies in 2008. Cavaletto, G.M., et al (2018) [6] found a lack of equal opportunity policies in the sample companies, as well as gender prejudice in promotions to senior positions. Øystein Strøm, R. (2015) [13] on the other hand, examined the impact of gender quotas on female board representation in Norway from 1989 to 2002 and discovered no discrimination during the study period.…”
Section: Review Literaturementioning
confidence: 94%
“…Another study conducted by Verma., N. (2015) [18] found gender discrimination exists in senior management positions in top 50 American sample companies in 2008. Cavaletto, G.M., et al (2018) [6] found a lack of equal opportunity policies in the sample companies, as well as gender prejudice in promotions to senior positions. Øystein Strøm, R. (2015) [13] on the other hand, examined the impact of gender quotas on female board representation in Norway from 1989 to 2002 and discovered no discrimination during the study period.…”
Section: Review Literaturementioning
confidence: 94%
“…The tendency to act based on superior's instruction. (Cavaletto et al, 2019) After an initial drive from management, the process started to change with the entire team of 102 following the advice of senior management.…”
Section: Chain Of Commandmentioning
confidence: 99%
“…The tendency to act based on superior's instruction (Cavaletto et al, 2019) After an initial drive from management, the process started to change with the entire team of 102 following the advice of senior management Change dilution The tendency to keep the process live to support the stakeholders and implement the required changes for correcting the issues (Cameron and Green, 2015) The team were committed to the requirement of keeping the process running and simultaneously undertaking specified improvements Change of job…”
Section: Chain Of Commandmentioning
confidence: 99%